LED display device
By using a dual continuous porous structure of the quantum dot film with a scattering enhancement effect in Micro-LED display devices, the problems of diffusion and optical crosstalk of quantum dot materials in the prior art are solved, and high brightness and low cost display effects are achieved.
Patent Information
- Application Number
- CN202010289215.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-04-14
AI Technical Summary
The existing quantum dot material is directly applied to the Micro-LED surface, which is prone to lateral diffusion during low-temperature thermal annealing, leading to optical crosstalk problems, and it is difficult to separate the close adhesion to Micro-LED, limiting the brightness and cost of the display device.
A quantum dot film with a bi-continuous porous structure with a scattering enhancement effect is used to modify the quantum dots through block copolymers and form a bi-continuous porous structure, which improves the absorption capacity of the quantum dot film to blue light and simplifies the structure of the display device.
It significantly improves the absorption capacity of the quantum dot film to LED blue light, improves the brightness of the display device, simplifies the structure, reduces costs, and improves the stability of the quantum dot film.
Smart Images

Figure CN111463199B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of display devices and relates to an LED display device. Background Art
[0002] Liquid crystal displays, active matrix organic light emitting diode panels (AMOLED), etc. are currently common small-sized displays. Currently common small-sized displays have limited brightness and cannot allow people to see the displayed images under strong light. With the widespread application of light-emitting diodes (LEDs) in the display and lighting fields, display devices composed of micron-level LED (MicroLED) chips can be used to replace the current common small-sized displays. Since the display device composed of LED chips has the characteristics of high brightness, it allows people to clearly see the displayed images under strong light.
[0003] Micro-LED is a miniaturized LED array structure with self-luminous display characteristics. Its technical advantages include full solid state, long life, high brightness, low power consumption, small size, ultra-high resolution, and can be used in extreme environments such as high temperature or radiation. Compared with OLED technology, which is also a self-luminous display, Micro-LED is not only more efficient and has a longer life, but the material is not easily affected by the environment and is relatively stable, and it can also avoid the phenomenon of afterimage.
[0004] CN 109411458A discloses a Micro-LED display device and a manufacturing method thereof. The MICRO LED display device comprises: a substrate, three Micro-LED chips, and three pieces of cured transparent adhesive; wherein each of the Micro-LED chips is connected to the substrate; each of the Micro-LED chips is covered with a piece of the cured transparent adhesive; and a plurality of red light quantum dots, a plurality of green light quantum dots, and a plurality of blue light quantum dots are mixed in the three pieces of the transparent adhesive.
[0005] CN 106356386A discloses an inkjet printing quantum dot display device of a Micro-LED array backlight source, comprising a Micro-LED substrate, on which a plurality of RGB pixel units arranged in an array are arranged, each RGB pixel unit comprising a red quantum dot unit, a green quantum dot unit and a transparent unit; the red quantum dot unit comprises a Micro-LED chip and a red quantum dot material, the red quantum dot material is excited by the blue light emitted by the Micro-LED chip to emit red light; the green quantum dot unit comprises a Micro-LED chip and a green quantum dot material, the green quantum dot material is excited by the blue light emitted by the Micro-LED chip to emit green light; the transparent unit comprises a Micro-LED chip and a transparent material, the transparent material is used to directly transmit the blue light emitted by the Micro-LED chip; a transparent material is arranged outside the RGB pixel unit for packaging.
[0006] CN 109979960A discloses a method for manufacturing a full-color Micro-LED display device based on a quantum dot light conversion layer, which relates to the technical field of display preparation. It solves the problem that the existing quantum dot material is directly coated on the Micro-LED surface. After the coating process is completed, the quantum dot material above the adjacent pixel units will diffuse laterally during the low-temperature thermal annealing process, and the mixing of different quantum dot materials will cause serious light crosstalk problems. The light source array and the quantum dot film layer are tightly adhered together, and there is a problem that it is difficult to separate. The light conversion layer substrate is prepared by applying quantum dot materials of different colors to different positions of a glass or polymer substrate in different areas. The monochrome Micro-LED display array is bonded to the light conversion substrate to achieve full-color display of Micro-LED. A DBR reflector is prepared at the bottom of the groove to suppress the emission of the monochrome Micro-LED array light source, thereby improving the utilization rate of the light source.
[0007] When existing quantum dot fluorescent films are used in combination with Micro-LEDs, the film thickness made of pure quantum dots is not easy to make thick, so it cannot fully absorb the blue light of Micro-LEDs. Therefore, in practical applications, it is necessary to combine it with filters, etc., which increases the cost of the device, makes it impossible to make ultra-thin devices, and complicates the processing technology. Summary of the invention
[0008] In view of the technical problems existing in the prior art, the present invention provides an LED display device, which uses a special quantum dot film with a double continuous porous structure with a scattering enhancement effect, which greatly improves the quantum dot film's ability to absorb blue light from LEDs, improves the brightness of the display device, and simplifies the structure of the LED display device.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] The present invention provides an LED display device, which includes a substrate and an LED array arranged on the substrate. The LED array includes an LED chip, and a bonding layer and a quantum dot film layer connected in sequence by the LED chip. The quantum dot film layer is a quantum dot film with a double continuous porous structure having a scattering enhancement effect.
[0011] In the present invention, the arrangement of LED chips in the LED array can be adjusted according to specific display requirements, and can be a rectangular array, a circular array, an elliptical array or an irregular array, etc. The spacing between each LED chip can be equal or unequal.
[0012] As a preferred technical solution of the present invention, the method for preparing the quantum dot film having a bicontinuous porous structure comprises the following steps:
[0013] (1) melt-kneading the first block copolymer and the second block copolymer, and cooling to obtain a mixture;
[0014] (2) dispersing the quantum dots in a solvent to obtain a quantum dot dispersion, and then adding the mixture obtained in step (1) to the quantum dot dispersion, stirring and removing the solvent to obtain block copolymer-modified quantum dots;
[0015] (3) Melting and pressing the block copolymer-modified quantum dots obtained in step (2) into sheets, and annealing to obtain a quantum dot film having a bicontinuous porous structure.
[0016] As a preferred technical solution of the present invention, the first block copolymer and the second block copolymer independently include any one of styrene-butadiene copolymer, styrene-isoprene copolymer, polytrihydroxybutyrate-polyethylene glycol copolymer, styrene-butadiene-styrene copolymer, styrene-butadiene-3-chloropropylene copolymer or polyethylene glycol-polycaprolactone-polyethylene glycol copolymer, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of styrene-butadiene copolymer and styrene-isoprene copolymer, a combination of styrene-isoprene copolymer and polytrihydroxybutyrate-polyethylene glycol copolymer, a combination of polytrihydroxybutyrate-polyethylene glycol copolymer and styrene-butadiene-styrene copolymer, a combination of styrene-butadiene-styrene copolymer and styrene-butadiene-3-chloropropylene copolymer, a combination of styrene-butadiene-3-chloropropylene copolymer and polyethylene glycol-polycaprolactone-polyethylene glycol copolymer, or a combination of polytrihydroxybutyrate-polyethylene glycol copolymer, styrene-butadiene-styrene copolymer and styrene-butadiene-3-chloropropylene copolymer;
[0017] The first block copolymer is different from the second block copolymer.
[0018] Preferably, the number average molecular weights of the first block copolymer and the second block copolymer are independently 1000 to 5000, such as 1000, 2000, 3000, 4000 or 5000, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In the present invention, the stable chemical bonding between quantum dots and block polymers, the block polymers also provide physical isolation protection, the structure is not easy to be destroyed, the influence of light, heat, and oxygen is reduced, and the working stability is improved; the composite material of quantum dots and block polymers can improve the dispersibility of quantum dots, control the distance between quantum dots, and reduce the efficiency reduction caused by fluorescence resonance energy transfer (FRET) after the quantum dots are prepared into thin films; the stability of the fluorescent film prepared by the blend of quantum dots and block polymers is good, and it is not necessary to combine other film protective layer materials or barrier layers, which can simplify the preparation process and reduce costs. In the present invention, by using more than two block polymers, combined with the preparation method, a bicontinuous porous structure is formed, and the scattering effect of the bicontinuous porous structure can promote the absorption of blue light (improve absorbance) and the emission of emitted fluorescence (improve light extraction efficiency), so that the blue light of LED can be fully absorbed, not only can the fluorescence intensity of the quantum dot fluorescent film be improved, and a high-brightness ultra-thin quantum dot fluorescent film be prepared, but also the product process and weight can be simplified, and the processing cost can be reduced, so as to realize the ultra-thinness of the display device.
[0020] As a preferred technical solution of the present invention, the temperature of the melt mixing in step (1) is 120-150°C, such as 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, in step (1), the mass ratio of the first front-stage copolymer to the second front-stage copolymer is 0.25 to 4:1, such as 0.25:1, 0.5:1, 0.75:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] As a preferred technical solution of the present invention, the quantum dots in step (2) include green light quantum dots or red light quantum dots;
[0023] Preferably, the green light quantum dots include any one of ZnS quantum dots, ZnSe quantum dots, CdS quantum dots, CdSe quantum dots, InP quantum dots or perovskite quantum dots.
[0024] Preferably, the red light quantum dots include any one of ZnS quantum dots, ZnSe quantum dots, CdS quantum dots, CdSe quantum dots, InP quantum dots or perovskite quantum dots.
[0025] Preferably, the blue light quantum dots include any one of ZnS quantum dots, ZnSe quantum dots, CdS quantum dots, CdSe quantum dots, InP quantum dots or perovskite quantum dots.
[0026] Preferably, the solvent in step (2) comprises any one of methanol, ethanol, tetrahydrofuran, ethyl acetate or acetone, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of methanol and ethanol, a combination of ethanol and tetrahydrofuran, a combination of tetrahydrofuran and ethyl acetate, a combination of ethyl acetate and acetone, a combination of acetone and ethanol, or a combination of ethanol, tetrahydrofuran and ethyl acetate.
[0027] Preferably, the concentration of the quantum dot dispersion in step (2) is 30 to 80 mg / mL, such as a combination of 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL or 80 mg / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] As a preferred technical solution of the present invention, the mass ratio of the mixed material in step (2) to the quantum dots is 5 to 20:1, such as 5:1, 6:1, 8:1, 10:1, 12:1, 15:1, 18:1 or 20:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the stirring time in step (2) is 24 to 48 hours, such as 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours or 48 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] As a preferred technical solution of the present invention, the temperature of the molten sheet in step (3) is 120-150°C, such as 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the time for melt pressing in step (3) is 1 to 3 minutes, such as 1 minute, 1.5 minutes, 2 minutes, 2.5 minutes or 3 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] As a preferred technical solution of the present invention, the annealing temperature in step (3) is 80-100°C, such as 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, 95°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the annealing time in step (3) is 10 to 20 min, such as 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] As a preferred technical solution of the present invention, the substrate includes any one of conductive glass, PET substrate, PI substrate and PEN substrate.
[0035] As a preferred technical solution of the present invention, the bonding layer includes a silicone resin adhesive and / or an epoxy resin adhesive.
[0036] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0037] The present invention provides an LED display device, which uses a special quantum dot film with a double continuous porous structure with a scattering enhancement effect, greatly improving the quantum dot film's ability to absorb blue light from LEDs, improving the brightness of the display device, and simplifying the structure of the LED display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a top view of the structure of the LED display device provided by the present invention;
[0039] Figure 2 It is a structural side view of the LED display device provided by the present invention.
[0040] In the figure: 1-substrate, 2-LED array, 3-LED chip, 4-adhesive layer, 5-quantum dot film layer.
[0041] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0043] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:
[0044] Example 1
[0045] This embodiment provides a method for preparing a quantum dot film having a bicontinuous porous structure, the method comprising the following steps:
[0046] (1) melt-mixing styrene-butadiene copolymer (molecular weight 1000) and polytrihydroxybutyrate-polyethylene glycol copolymer (molecular weight 2000) at a mass ratio of 0.25:1 at 120° C., and cooling to obtain a mixture;
[0047] (2) dispersing CdSe quantum dots in ethanol to obtain a quantum dot dispersion liquid, wherein the concentration of the quantum dot dispersion liquid is 30 mg / mL, and then adding the mixture obtained in step (1) to the quantum dot dispersion liquid, wherein the mass ratio of the mixture to the quantum dots is 5:1, and stirring for 24 hours and then removing the solvent to obtain block copolymer-modified quantum dots;
[0048] (3) The block copolymer modified quantum dots obtained in step (3) are melt-pressed at 120° C. for 3 min, and annealed at 80° C. for 20 min to obtain a quantum dot film with a bicontinuous porous structure.
[0049] Example 2
[0050] This embodiment provides a method for preparing a quantum dot film having a bicontinuous porous structure, the method comprising the following steps:
[0051] (1) melt-mixing styrene-butadiene-3-chloropropylene copolymer (molecular weight 5000) and ethylene glycol-polycaprolactone-polyethylene glycol (molecular weight 5000) at a mass ratio of 4:1 at 150° C., and cooling to obtain a mixture;
[0052] (2) dispersing ZnS quantum dots in ethyl acetate to obtain a quantum dot dispersion liquid, wherein the concentration of the quantum dot dispersion liquid is 50 mg / mL, and then adding the mixture obtained in step (1) to the quantum dot dispersion liquid, wherein the mass ratio of the mixture to the mass of the quantum dots is 10:1, and stirring for 36 hours and then removing the solvent to obtain block copolymer-modified quantum dots;
[0053] (3) The block copolymer modified quantum dots obtained in step (3) are melt-pressed at 150° C. for 1 min, and annealed at 90° C. for 15 min to obtain a quantum dot film with a bicontinuous porous structure.
[0054] Example 3
[0055] This embodiment provides a method for preparing a quantum dot film having a bicontinuous porous structure, the method comprising the following steps:
[0056] (1) melt-mixing styrene-butadiene copolymer (molecular weight 3000) and ethylene glycol-polycaprolactone-polyethylene glycol (molecular weight 3000) at a mass ratio of 1:1 at 130° C., and cooling to obtain a mixture;
[0057] (2) dispersing ZnSe quantum dots in ethyl acetate to obtain a quantum dot dispersion liquid, wherein the concentration of the quantum dot dispersion liquid is 60 mg / mL, and then adding the mixture obtained in step (1) to the quantum dot dispersion liquid, wherein the mass ratio of the mixture to the quantum dots is 8:1, and stirring for 30 hours before removing the solvent to obtain block copolymer-modified quantum dots;
[0058] (3) The block copolymer modified quantum dots obtained in step (3) are melt-pressed at 140° C. for 2 min, and annealed at 80° C. for 12 min to obtain a quantum dot film with a bicontinuous porous structure.
[0059] Example 4
[0060] Except for replacing ZnSe quantum dots with ZnS quantum dots, other conditions in this embodiment are the same as those in Embodiment 3.
[0061] Example 5
[0062] Except that ZnSe quantum dots are replaced by CdSe quantum dots, other conditions in this embodiment are the same as those in Embodiment 3.
[0063] The specific implementation method of the present invention is to illustrate the technical effect of the present application by taking the LED display device in the LED display device as an example.
[0064] Example 6
[0065] This embodiment provides an LED display device, whose structure is as follows Figure 1 and Figure 2 As shown, the display device includes a substrate 1 and an LED array 2 arranged on the substrate, the LED array 2 includes 9 LED chips 3, and an adhesive layer 4 and a quantum dot film layer 5 connected in sequence by the LED chips, and the quantum dot film layer 5 is a quantum dot film with a double continuous porous structure prepared in Example 3.
[0066] Example 7
[0067] This embodiment provides an LED display device, whose structure is as follows Figure 1 and Figure 2As shown, the display device includes a substrate 1 and an LED array 2 arranged on the substrate, the LED array 2 includes 9 LED chips 3, and an adhesive layer 4 and a quantum dot film layer 5 connected in sequence by the LED chips, and the quantum dot film layer 5 is a quantum dot film with a double continuous porous structure prepared in Example 4.
[0068] Example 8
[0069] This embodiment provides an LED display device, whose structure is as follows Figure 1 and Figure 2 As shown, the display device includes a substrate 1 and an LED array 2 arranged on the substrate, the LED array 2 includes 9 LED chips 3, and an adhesive layer 4 and a quantum dot film layer 5 connected in sequence by the LED chips, and the quantum dot film layer 5 is a quantum dot film with a double continuous porous structure prepared in Example 5.
[0070] Example 9
[0071] This embodiment provides an LED display device, whose structure is as follows Figure 1 and Figure 2 As shown, the display device includes a substrate 1 and an LED array 2 arranged on the substrate, the LED array 2 includes 9 LED chips 3, and a bonding layer 4 and a quantum dot film layer 5 connected in sequence by the LED chips, and the first row to the third row in the LED array 2 use quantum dot films with a double continuous porous structure prepared in Example 3, Example 4 and Example 5 in sequence from top to bottom.
[0072] Comparative Example 1
[0073] In this comparative example, except that ethylene glycol-polycaprolactone-polyethylene glycol (molecular weight 3000) was replaced by an equal mass of styrene-butadiene copolymer (molecular weight 3000) when preparing the quantum dot film, other conditions were the same as those of Example 3.
[0074] Comparative Example 2
[0075] In this comparative example, except that the styrene-butadiene copolymer (molecular weight 3000) was replaced by an equal mass of ethylene glycol-polycaprolactone-polyethylene glycol (molecular weight 3000) when preparing the quantum dot film, other conditions were the same as those in Example 3.
[0076] Comparative Example 3
[0077] This comparative example provides an LED display device. Except that the quantum dot film layer uses the quantum dot film provided in comparative example 1, other conditions are the same as those in example 4.
[0078] Comparative Example 4
[0079] This comparative example provides an LED display device. Except that the quantum dot film layer uses the quantum dot film provided in comparative example 2, other conditions are the same as those in example 4.
[0080] The normalized fluorescence intensity of the LED display devices provided in Examples 6-9 and Comparative Examples 3 and 4 was tested, and the results are shown in Table 1. The above LED chip emits 450nm blue light during the test.
[0081] Table 1
[0082] Normalized fluorescence intensity / au Example 6 1 Example 7 0.96 Example 8 0.92 Example 9 0.95 Comparative Example 3 0.08 Comparative Example 4 0.10
[0083] From the test results in Table 1, it can be seen that the normalized fluorescence intensity of the LED display device provided by the present application is 1, which proves that the LED display device can fully utilize the blue light emitted by the LED compared with the devices in other embodiments. However, in Comparative Examples 3 and 4, ethylene glycol-polycaprolactone-polyethylene glycol copolymer and styrene-butadiene copolymer were not used in the preparation of quantum dot films, which greatly reduced the utilization rate of the blue light emitted by the LED by the LED display device.
[0084] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0085] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0086] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0087] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. An LED display device, characterized in that: The display device comprises a substrate and an LED array arranged on the substrate, wherein the LED array comprises an LED chip, and a bonding layer and a quantum dot film layer sequentially connected by the LED chip, wherein the quantum dot film layer is a quantum dot film with a double continuous porous structure having a scattering enhancement effect; The method for preparing the quantum dot film with a bicontinuous porous structure having a scattering enhancement effect comprises the following steps: (1) melt-kneading the first block copolymer and the second block copolymer, and cooling to obtain a mixture; (2) dispersing the quantum dots in a solvent to obtain a quantum dot dispersion, and then adding the mixture obtained in step (1) to the quantum dot dispersion, stirring and removing the solvent to obtain block copolymer-modified quantum dots; (3) melting and pressing the block copolymer-modified quantum dots obtained in step (2) into sheets, and annealing to obtain a quantum dot film having a bicontinuous porous structure; The first block copolymer and the second block copolymer independently include any one of styrene-butadiene copolymer, styrene-isoprene copolymer, polytrihydroxybutyrate-polyethylene glycol copolymer, styrene-butadiene-styrene copolymer, styrene-butadiene-3-chloropropylene copolymer or polyethylene glycol-polycaprolactone-polyethylene glycol copolymer or a combination of at least two thereof; The first block copolymer is different from the second block copolymer; The number average molecular weights of the first block copolymer and the second block copolymer are independently 1000 to 5000; The annealing temperature in step (3) is 80-100° C., and the annealing time is 10-20 min.
2. The display device according to claim 1, characterized in that The temperature of the melt kneading in step (1) is 120-150°C.
3. The display device according to claim 1, characterized in that In step (1), the mass ratio of the first block copolymer to the second block copolymer is 0.25 to 4:
1.
4. The display device according to claim 1, characterized in that The quantum dots in step (2) include green light quantum dots or red light quantum dots; The green light quantum dots include any one of ZnS quantum dots, ZnSe quantum dots, CdS quantum dots, CdSe quantum dots, InP quantum dots or perovskite quantum dots; The red light quantum dots include any one of ZnS quantum dots, ZnSe quantum dots, CdS quantum dots, CdSe quantum dots, InP quantum dots or perovskite quantum dots; The solvent in step (2) includes any one of methanol, ethanol, tetrahydrofuran, ethyl acetate or acetone, or a combination of at least two thereof.
5. The display device according to claim 1, characterized in that The concentration of the quantum dot dispersion in step (2) is 30 to 80 mg / mL.
6. The display device according to claim 1, characterized in that The mass ratio of the mixed material in step (2) to the quantum dots is 5 to 20:
1.
7. The display device according to claim 1, characterized in that The stirring time in step (2) is 24 to 48 hours.
8. The display device according to claim 1, characterized in that The temperature of the melt-pressed sheet in step (3) is 120-150°C.
9. The display device according to claim 1, characterized in that: The time for melting and tableting in step (3) is 1 to 3 minutes.
10. The display device according to claim 1, characterized in that The substrate includes any one of conductive glass, PET substrate, PI substrate and PEN substrate.
11. The display device according to claim 1, characterized in that The bonding layer includes a silicone resin bonding agent and / or an epoxy resin bonding agent.
Citation Information
Patent Citations
Micro-LED (Micro-light emitting diode) array backlight source-based ink-jet printing quantum dot display device
CN106356386A
MICRO LED display device and manufacturing method thereof
CN109411458A
Manufacturing method of full-color Micro-LED display device based on quantum dot photo-conversion layer
CN109979960A
Polymer composition
CN109983044A
Quantum dot compound and preparation method thereof
CN110551496A